Shopping mobile application on Apple iOS - Singh, Nidhi (2016)
In today’s smartphone-savvy markets, majority of the human population prefers usage of user-friendly mobile applications to provide them with services in an efficient manner. According to a research study by data analytics company, Nielsen, users between the ages of 25-44 years use an average of 29 applications per month [1]. It is estimated that nearly 2 billion people use smartphones today and this number is expected to grow to 3 billion by 2018 [2].